El estrés laboral y su relación con el consumo de sustancias psicoactivas en los Militares en el Grado de Cabo Segundo del Fuerte Militar Miguel Iturralde de la ciudad de Loja, periodo 2019 - Pucha Sánchez, Esperanza del Cisne (2020)
The following investigation research was prepared with the objective to determine the relationship between job stress and the consumption of psychoactive substances in the staff that work at the Military in the Second-Degree Rank from “Miguel Iturralde Military Fort” from the city of Loja. Research desing was transversal, not experimental and quantitative- qualitative. The sample was conformed by 80 military employees with a Second-Degree Rank from the “Miguel Iturralde Military Fort”, to whom were appplied the Work Stress Questionnaire from the World Health Organization and the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) from the World Health Organization, information was collected and then tabulated and analyzed through the IBM SPSS Statistics 25 Program by using descriptive statistics. A statistically significant relationship was found in the results (p= 0.0001) between job stress and the consumption of psychoactive substances from the participants, the 67.50% of the participants showed a low rate of job stress and a low risk of consumption of psychoactive substances; the 16.30% of the participants showed an intermediate job stress and a moderate risk to the consumption of psychoactive substances, instead, the 2.5% of the participants showed a severe job stress and a moderate risk to the consumption of psychoactive substances, and no participants showed a high job stress. There were found some limitations in the development of this research, the conclusions of this research about stress and the consumption of psychoactive substances are limited for men, in addition it is limited to explain the functioning of these variables in Military with a Second-Degree rank without considering other Military ranks. For future research it is recommended to consider other variables of interest such as age, profession field, gender in the correlation between stress and the consumption of psychoactive substances. Key-words: job stress, psychoactive substances risk, correlation